From Arrival to Citizenship: Reviewing the Multicultural Model of Swedish Refugees' Integration Policy - Yusuf Abubakar WARA (International Journal of Social Science and Human Research, 2025)
This study examines Sweden’s refugee integration model, tracing the trajectory from initial reception to full citizenship. Drawing on Castles and Miller’s trichotomous framework of immigrant integration, it investigates how Sweden’s historically multicultural policies have shaped refugees’ access to social and cultural support, education and language acquisition, labour market participation, and citizenship rights. Using meta-synthesis methodology, the study reviews 52 relevant sources, including core peer-reviewed articles retrieved from the Web of Science, Clarivate, and Taylor & Francis Online (2000–2025). Findings reveal that Sweden's longstanding multicultural approach has enabled refugees to integrate effectively and access pathways to citizenship more readily than in most European states. However, recent policy shifts toward restrictive measures that include stricter residency requirements, language proficiency tests, and financial thresholds signal a move toward assimilationist tendencies. This transformation reflects broader political realignments driven by rising populism and European anti-immigration rhetoric. The article contributes to migration scholarship by offering a comprehensive framework for analysing the continuum of refugee integration and citizenship acquisition, while providing policy recommendations for balancing humanitarian obligations with political and social pressures.
Keywords: Citizenship, Integration, Multicultural, Refugee, Sweden